Declining adult survival of New Zealand Bar-tailed Godwits during 2005–2012 despite apparent population stability. (1st June 2016) - Conklin, Jesse R.; Lok, Tamar; Melville, David S.; Riegen, Adrian C.; Schuckard, Rob; Piersma, Theunis; Battley, Phil F.
Abstract: Like many migratory shorebird populations using the East Asian—Australasian Flyway, Bar-tailed Godwits Limosa lapponica baueri in New Zealand have significantly declined since the mid-1990s, but census data indicate a relatively stable population since 2004. The demographic drivers of both the decline and stabilisation remain unknown. We estimated annual survival from mark—recapture data of adult godwits in New Zealand during 2005–2014. Annual adult survival declined over the study period from 0.89-0.96 in 2005–2010 to 0.83-0.84 in 20112012. The simultaneous decline in annual survival found in a separate study of Bar-tailed Godwits L. l. menzbieri in north-west Australia suggests a common effect of their high dependence on threatened migratory staging sites in the Yellow Sea; the more extreme decline in L. l. menzbieri may reflect ecological differences between the populations, such as timing and extent of use of these sites. At current apparent recruitment rates, persistent adult survival of ∼0.84 would lead to a population decline of 5–6% per year in L. l. baueri. Our study implies that the demographic precursors to a population decline developed during a period of apparent population stability; this suggests that monitoring a single index of population stability is insufficient for predicting future trends.